Pengaruh Konsentrasi Filler Serat Daun Nanas (Ananas comosus) Dan PVA (Polivinil Alkohol) Pada Sintesis Bioplastik Dari Pati Biji Nangka - Pane, Dewi Sriana S; Amri, Idral; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pineapple leaf fiber consists of about 70-80% wt cellulose giving its high tensile strength and elastic modulus for bioplastics. To increased the elongation of bioplastic, starch has to be mixed with other synthetic polymers such as polyvinyl alcohol (PVA). The aimed of this research was to determine the effect of various pineapple leaf fiber and polyvinyl alcohol (PVA) concentration to the mechanical properties (tensile strength, elongation, modulus young and tear strength), water uptake, biodegradation and morphology. Bioplastics were made by mixing of starch of jackfruit seed, water, filler and plasticizer with variation of fiber were 0 (%w/w), 2 (%w/w), 4 (%w/w), 6 (%w/w), 8 (%w/w), and 10 (%w/w) and ratios starch: polyvinyl alcohol (PVA) were 1:1 and 1:1,5. The results revealed that the filler fiber and PVA gave an impact to mechanical properties of bioplastic, the best mechanical properties was on bioplastic with composition starch:PVA 1:1 and filler 8 (%w/w) with tensile strength 15,79 MPa, and modulus young 1967,01 MPa and tear strength 3,4021 Kgf. The best water uptake of bioplastic is 32,5 % and the fastest degradation time on bioplastic with composition fiber 10 (%w/w) and ratio starch:PVA 1:1,5 in 7 days. SEM analysis showed that filler distribution was not spreading evenly on matrices. Keywords: jackfruit seed, bioplastic, starch, polyvinyl alcohol, pineapple leaf fiber